Narratives for Business Processes-based Digital Games: Systematic Mapping of the Literature - Ferreira, Márcio Rocha; Classe, Tadeu Moreira de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: Digital games can be considered information systems because they use technological resources to interact with people, process data, and create outputs. Moreover, Business Processes-based Digital Games (JDBPN) are a game genre used to learn and understand business processes in an organization, associating their goals with fun and ludicity. For this, the JDBPN’ elements need to approach business processes’ aspects correctly. Problem: Among these elements, narratives can be helpful to present the process’ instances and their details to the players. However, designing these narratives is a challenge. Solution: This article aims to identify methods, frameworks, and proposals to help the creation of narratives for JDBPN. Method: The research methodology followed a systematic mapping of the literature. However, as JDBPN is a new theme, there was a need to execute the mapping in two steps: i) narratives from games with a purpose and ii) narratives related to business processes. Summary of Results: As a result, we found 794 studies that, after analysis, we selected 14 studies. By the snowballing technique, we added 10 more studies. All of those 24 studies present relevant features for designing narratives for JDBPN. Contributions to IS: Hence, this research contributes to information systems and their dimensions, since we approach the understanding of business processes (organizations), how the players (professionals, clients, or business partners) face the processes problems, and, also, focusing on the narrative design as an element for the engineering of the digital game (technology).